Le substrat spécialisé de la « hard science fiction » au miroir de la fiction à substrat professionnel : essai de caractérisation - Marion Pujalte; Anthony Saber (ReS Futurae)
Relying on the conceptual frameworks used in English for specific purposes to describe fiction à substrat professionnel (FASP), a type of novel which highlights professional or disciplinary content, we propose a characterization of the specialized substratum present in ten major works considered to be emblematic of hard science fiction. The latter has indeed many editorial ties with FASP, a literary genre defined by Michel Petit (1999) as a “pathway” to the knowledge, procedures and the language of professional circles : in both genres, authors enjoy expert status, disciplinary knowledge is significantly present, a desire for popularization can clearly be perceived, the literary aesthetic is resolutely descriptive, and specialized aspects actually drive the plot. Building on similarities with FASP, we identified five types of specialized substratum in hard SF, each illustrative of a certain degree of proximity or distance with respect to current scientific knowledge : the mirror/analog substratum, the incrementally extrapolated substratum, the breakthrough substratum, the semi-speculative substratum, and the pseudo-scientific speculative substratum.